Treatment of a Gastric Lactobezoar with N-Acetylcysteine. (20th November 2014) - Sparks, Brandon; Kesavan, Anil
Abstract : Lactobezoars are a rare finding with potentially serious sequelae in pediatric patients with feeding intolerance. Aggressive treatment may be preferred to traditional treatments to avoid complications in medically complex patients. In our patient, N-acetylcysteine lavage was a safe and effective alternative that resulted in rapid resolution of his feeding intolerance.